Halal Value Chain of Processed Fish Food: Case Study of Pempek and Tekwan - Pratiwi, Heni; Purwanto, Purwanto (Universitas Pendidikan Indonesia, 2024)
Purpose – This study aims to simulate a Halal Value Chain for processed fish food products achieving halal certification standards. The products we chose were Pempek and Tekwan which are the most processed fish foods in Jambi City.Methodology - This study is qualitative research. Halal Value Chain of processed fish food products is simulated by using data from MSMEs owning Halal Certification. We conduct the research with three stages. The first stage was determining the MSMEs that would be researched, where the business products had received a BPJPH halal certificate, the second stage was observing and identifying production houses and the third stage was processing the data and information that had been obtained and simulating a halal value chain.Findings -. We have succeeded in simulating a Halal Value Chain for processed fish food products, especially for Pempek and Tekwan products by MSMEs owning Halal Certification. This simulation can be used for the same business, we also found that the halal value chain in processed fish food should always be maintained by halal management. MSMEs needs to create operational standards in monitoring and evaluating the halal value chain.Keywords: Halal Value Chain, Halal Certification, Processed Fish Food, Pempek and Tekwan